Enantioselective remote C–H activation directed by a chiral cation - Genov, Georgi R.; Douthwaite, James L.; Lahdenperä, Antti S. K.; Gibson, David C.; Phipps, Robert J. (Science (American Association for the Advancement of Science), 2020)
Numerous positively charged metal catalysts have been paired with chiral negative ions to select for just one of two mirror-image products. Genov et al. now report a potentially general strategy to invert the charges in this paradigm. Because intrinsically negative metal catalysts are comparatively rare, the authors appended a sulfonate group to the common bipyridyl ligand. Iridium complexes of this ligand paired with chiral positive ions could borylate just one of two aryl rings appended to carbon or phosphorus centers with high enantioselectivity. Science , this issue p. 1246 Sulfonating a bipyridyl ligand offers a versatile approach for ion-pairing transition metal catalysts with chiral cations. Chiral cations have been used extensively as organocatalysts, but their application to rendering transition metal–catalyzed processes enantioselective remains rare. This is despite the success of the analogous charge-inverted strategy in which cationic metal complexes are paired with chiral anions. We report here a strategy to render a common bipyridine ligand anionic and pair its iridium complexes with a chiral cation derived from quinine. We have applied these ion-paired complexes to long-range asymmetric induction in the desymmetrization of the geminal diaryl motif, located on a carbon or phosphorus center, by enantioselective C–H borylation. In principle, numerous common classes of ligand could likewise be amenable to this approach.